LOW VELOCITY IMPACT ANALYSIS ON COMPOSITE MATERIAL - C. Anand, K. Srinivasan, ChristuRajan M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This project aims at experimentally studying low velocity impact on fiber reinforced glass sheets. An experimental setupis fabricated, wherein a dart of known mass with accelerometer inbuilt in it made to fall on specimens of fiber reinforced glasssheets.The damageof thesheets of various thicknesses for various kinetic energies ofdart is studied.The kinetic energy isvaried by altering the height of the dart above the specimen sheet. The amount of energy transferred from the dart to the sheet ismeasured by the accelerometer output. The kinetic energy of the dart just before the moment it strikes the sheet is calculated bysimple formula. The energyabsorbed by thesheetis proportional to the thickness,material characteristics and the kineticenergy of the dart during collision. The dart is made fall free on the sheet; therefore, the acceleration is constant and is equal tothe acceleration due to gravity constant (9.8 m sec-2). Since the height of the dart above the sheet does not exceed three meters,the velocity during collision is comparatively low. A tabulation of velocities of dart, thickness of sheets and obtained. Theaccelerometer’s electrical output is signal conditioned and is displayed in a computed using appropriate software. The goal ofthis project is to get a complete knowledge of the low velocity impact on the glass reinforced fiber sheets and to conclude howfeasibleitcanbeforvariousapplications.